Knowledge, attitude and practice on dengue fever prevention in Perak Tengah district / Mohammad Nasir Abdullah …[et al.] - Abdullah, Mohammad Nasir; Wan Azib, Wan Nor Hazimah; Burhanuddin, Muhamad Addin; Mohd Harun, Mohd Fauzi (Prof. Madya. Dr. ) (2013)
Dengue is a mosquito-borne infection that had become a major public health concern. It is a disease found in most tropical and subtropical areas of the world and had become the most common arboviral disease of human. Dengue fever is an acute febrile disease due to a viral infection and presents with severe headache, pain in the eyes, high fever, backache, vomiting, muscle and joint pain as well as rash. It also known as Dengue Haemorrhagic Fever. Based on the report from Ministry of Health Malaysia, the dengue fever cases was shown an increasing trend from 1996 until 2007. The incidence rate also shows an upward trend from 44.3 cases per 100,000 populations in 1999 to 181 cases per 100,000 populations in 2007. This exceeds the national target for the incidence rate of Dengue Fever which is less than 50 cases per 100,000 populations. Furthermore, most of the dengue cases reported from urban areas where there is a high density of its population and rapid development activities factors which favour dengue transmission. The objective was to assess the knowledge, attitude and practice of the people regarding dengue fever in Perak Tengah district, Perak. The study design was cross sectional study with concerning the knowledge, attitude and practices of the dengue fever prevention among the people in Perak Tengah district, Perak. The inclusion criteria were all residents who living Perak Tengah district for at least one year and age between 18 and 60 years old. The sample size after considered 10% of missing data are for case group it will be 199 respondents. The type I error probability associated with this test of the null hypothesis is 0.05 with the 80% power of the study. The result for this study can be used as guideline in planning for more effective and reliable solution to health problems in relation to dengue fever.